Metal-organic framework and inorganic glass composites - Longley, Louis; Calahoo, Courtney; Limbach, René; Xia, Yang; Tuffnell, Joshua M.; Sapnik, Adam F.; Thorne, Michael F.; Keeble, Dean S.; Keen, David A.; Wondraczek, Lothar; Bennett, Thomas D. (Nature communications, 2020)
Metal-organic framework (MOF) glasses have become a subject of interest as a distinct category of melt quenched glass, and have potential applications in areas such as ion transport and sensing. In this paper we show how MOF glasses can be combined with inorganic glasses in order to fabricate a new family of materials composed of both MOF and inorganic glass domains. We use an array of experimental techniques to propose the bonding between inorganic and MOF domains, and show that the composites produced are more mechanically pliant than the inorganic glass itself. Metal-organic frameworks constitute a family of glass formers that is distinct from those that are polymeric, metallic, or inorganic. Here the authors show that they can be combined with different inorganic aluminophosphate glasses to produce a composite with mechanical properties intermediate between the two end-members.